Recycling of glazed roof tile waste for fine aggregate in green concrete - Mohamad Juoi, Jariah; Yusuf, Yusliza; Mohd Rosli, Zulkifli; Mustafa, Nuzaimah; Wan Zulkifli, Wan Amirul Shafiz; Abdul Aziz, Fariha Awatif; Abd. Wahab, Nur Umairah Afifah (2023)
Glazed Roof Tile Waste (GRTW) is identified as having the potential to replace the natural sand aggregate used in cement mixture. This is an innovative effort to produce green concrete. The produced green concrete is intended for building materials application, used for the construction of buildings, drainage, paving, and landscaping. The purpose of this paper is to report on the workability of the concrete mixture, physical characteristics, and compression strength of the green concrete produced. Work involved in this research starts with a preparation of the GRTW thru grinding and milling. The crushed GRTW was sieved and analyzed according to BS 882:1992. Next, the GRTW with different weight fraction (10, 20, and 50%) was mixed with sand, cement, and water to identify its workability thru slump test (BS EN 12350-2). The mixture with accepted workability was casted into concrete specimen (100 mm×100 mm×100 mm) and subjected to compression test for 7 and 28 days, and the compressive strength results were compared with Gred M 25 concrete standard. It was found that the workability of concrete mixture gradually increases with the increases of GRTW weight fraction of 10 and 20%, however the workability decrease below the acceptable workability with 50% replacement of GRTW. Hence, the substitution of 20% of GRTW had been proven to have better mechanical performance in term of the slump value achieved, water absorption and compressive strength and can replace sand as fine aggregate in concrete.